From Nitrate to Nitric Oxide: The Role of Salivary Glands and Oral Bacteria. (December 2016) - Qu, X.M.; Wu, Z.F.; Pang, B.X.; Jin, L.Y.; Qin, L.Z.; Wang, S.L.
The salivary glands and oral bacteria play an essential role in the conversion process from nitrate (NO3 - ) and nitrite (NO2 - ) to nitric oxide (NO) in the human body. NO is, at present, recognized as a multifarious messenger molecule with important vascular and metabolic functions. Besides the endogenous L-arginine pathway, which is catalyzed by complex NO synthases, nitrate in food contributes to the main extrinsic generation of NO through a series of sequential steps (NO3 - -NO2 - -NO pathway). Up to 25% of nitrate in circulation is actively taken up by the salivary glands, and as a result, its concentration in saliva can increase 10- to 20-fold. However, the mechanism has not been clearly illustrated until recently, when sialin was identified as an electrogenic 2NO3 - /H + transporter in the plasma membrane of salivary acinar cells. Subsequently, the oral bacterial species located at the posterior part of the tongue reduce nitrate to nitrite, as catalyzed by nitrate reductase enzymes. These bacteria use nitrate and nitrite as final electron acceptors in their respiration and meanwhile help the host to convert nitrate to NO as the first step. This review describes the role of salivary glands and oral bacteria in the metabolism of nitrate and in the maintenance of NO homeostasis. The potential therapeutic applications of oral inorganic nitrate and nitrite are also discussed.